Analisis Pengendalian Kualitas Produk Yoghurt Pada KPSBU Lembang - Azmi, Widya Noer; Murdani, Denny (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze (1) The implementation of Good Manufacturing Practices (GMP) carried out by KPSBU Lembang. (2) Factors that cause discrepancies in the application of Good Manufacturing Practices (GMP) at KPSBU Lembang. The research method used in this research uses descriptive qualitative methods, by collecting information data through interviews, documentation, and observation. This type of research data uses Primary data and Secondary data. Primary data, is data collected by conducting interviews and observations directly from the source. Secondary data is data obtained in finished form, such as the internet and various existing documents. The results showed that the implementation of product quality control at KPSBU Lembang was partly in accordance but partly still not in accordance with the GMP Guidelines of the Minister of Health Regulation No.23 / MEN. KES/SK/1978. The results of the analysis of the factors that cause non-conformity of GMP implementation using the cause and effect diagram are caused by the man factor caused by inappropriate employee sanitation facilities and lack of awareness of employee hygiene. From the Environment factor caused by the selection of inappropriate production sites and the layout of the processing room which is less spacious and inappropriate. From the Machine factor caused by equipment that is rarely cleaned, as well as irregular storage and lack of a special laboratory room for the testing process. Meanwhile, the Method factor is caused by the fact that no organoleptic, physical, chemical, microbiological and / or biological examination has been carried out on the ingredients used, besides that the production room has a lot of dust and dirt.